Potential for positive biodiversity outcomes under diet-driven land use change in Great Britain [version 2; peer review: 2 approved] - Amber Wheeler; Patricia Eustachio Colombo; Alan D Dangour; Anna Taylor; Pauline Scheelbeek; Richard G Pearson; Georgina Mace; Owen Nicholas; Henry Ferguson-Gow; Rosie Green; Charlotte Outhwaite (Wellcome Open Research, 2024)
Background A shift toward human diets that include more fruit and vegetables, and less meat is a potential pathway to improve public health and reduce food system-related greenhouse gas emissions. Associated changes in land use could include conversion of grazing land into horticulture, which makes more efficient use of land per unit of dietary energy and frees-up land for other uses. Methods Here we use Great Britain as a case study to estimate potential impacts on biodiversity from converting grazing land to a mixture of horticulture and natural land covers by fitting species distribution models for over 800 species, including pollinating insects and species of conservation priority. Results Across several land use scenarios that consider the current ratio of domestic fruit and vegetable production to imports, our statistical models suggest a potential for gains to biodiversity, including a tendency for more species to gain habitable area than to lose habitable area. Moreover, the models suggest that climate change impacts on biodiversity could be mitigated to a degree by land use changes associated with dietary shifts. Conclusions Our analysis demonstrates that options exist for changing agricultural land uses in a way that can generate win-win-win outcomes for biodiversity, adaptation to climate change and public health.